2003
DOI: 10.1139/p02-125
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric characterization of coals

Abstract: Application of an electromagnetic analysis for coal characterization is attempted. By time domain reflectometry (TDR), dispersion spectra in the DC – 5 GHz range of a wide variety of coals are obtained for room temperature. Static permittivity and relaxation frequency of the different samples are compared with parameters obtained by chemical analysis. Comparison reveals the usefulness of the electromagnetic characterization for the establishment of coal rank, and shows how an analysis of the dielectric charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Therefore, after the raw coal loses water, the coal dielectric constant reaches a minimum. Carbon-carbon π-bonds exist between aromatic carbon layers, and the electron of the π-bond in crystalline carbon was a type of localized electron [39][40][41] . Localized electrons remain in localized sites most of the time, but can occasionally jump to neighboring localized sites, which could lead to polarization under certain boundary conditions.…”
Section: Changes In the Functional Groups Of Oxidized Coal The Type mentioning
confidence: 99%
“…Therefore, after the raw coal loses water, the coal dielectric constant reaches a minimum. Carbon-carbon π-bonds exist between aromatic carbon layers, and the electron of the π-bond in crystalline carbon was a type of localized electron [39][40][41] . Localized electrons remain in localized sites most of the time, but can occasionally jump to neighboring localized sites, which could lead to polarization under certain boundary conditions.…”
Section: Changes In the Functional Groups Of Oxidized Coal The Type mentioning
confidence: 99%
“…(Balanis et al 1980;Marland et al 2001;Forniés-Marquina et al 2003). Thus, it is hard to accurately measure the dielectric properties and the test results obtained by different scholars are usually inconsistent.…”
Section: Test Of Complex Dielectric Constant Of Coalmentioning
confidence: 99%
“…Forniés-Marquina et al (2003) has shown that when the sulphur content was higher than 4 % the coal relaxation frequency would decreased with the increase of sulphur content, which might contribute to microwave absorption.…”
Section: Responses Of Coal and Sulphur-containing Constituents To Micmentioning
confidence: 99%
“…It has also been determined that high-pressure water vapor (microwave frequency 2.45 GHz, microwave power 1 kW, irradiation time 240 s, coal sample temperature 222 °C, relative atmospheric pressure 1.54 kPa) in the pore structure may cause pore deformation, destruction, and interconnection [20,21]. The moisture present in the coal reservoir displays a dielectric loss greater than that in the coal matrix; therefore, it may be selectively heated using microwaves [22][23][24]. We have also previously shown that the water contained in coal rocks can be quickly heated under microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%